1995
DOI: 10.1007/bf00298241
|View full text |Cite
|
Sign up to set email alerts
|

The Graf stabilisation system: early results in 50 patients

Abstract: The results of the first 50 consecutive patients using the Graf stabilisation system are presented. The average age of the patients was 41 years; there were 32 women and 18 men in the group. All patients suffered from intractable symptomatic degenerative disc disease which could be localised to one or more levels. All patients gave a history of chronic back pain, but the mean period of severe disability was 24 months. The mean preoperative disability score (Oswestry questionnaire) was 59%. The average period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 15 publications
1
58
0
3
Order By: Relevance
“…The first pedicle screw-based system was likely the Graf ligamentoplasty, which used knitted Dacron bands (INVISTA, Wichita, KS, USA) to lock the facet joints in extension and thus limit flexion [18,19]. Although positive short-term results were obtained in carefully selected young patients, long-term follow-up results were not encouraging [20,21]. The Dynesys (Zimmer, Winterthur, Switzerland) is a popular device using titanium alloy pedicle screws and polycarbonate urethane spacers that surround tensioned polyethylene terephtalate (PET) cords on each side in order to reduce facet joint loading [22].…”
Section: Discussionmentioning
confidence: 99%
“…The first pedicle screw-based system was likely the Graf ligamentoplasty, which used knitted Dacron bands (INVISTA, Wichita, KS, USA) to lock the facet joints in extension and thus limit flexion [18,19]. Although positive short-term results were obtained in carefully selected young patients, long-term follow-up results were not encouraging [20,21]. The Dynesys (Zimmer, Winterthur, Switzerland) is a popular device using titanium alloy pedicle screws and polycarbonate urethane spacers that surround tensioned polyethylene terephtalate (PET) cords on each side in order to reduce facet joint loading [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, to solve the complication of ASD several flexible or even dynamic devices have been used with controversial results [17,43,50,52]. It has been proposed that non-fusion motion preservation surgery may prevent accelerated ASD because of the protective effects of continuing segmental motion.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them (Graf, Dynesys) were secured to the spine by pedicle screw fixation systems [17], while other implants are secured in the interspinous space [38,48]. Although early results of pedicle-screw systems of flexible intervertebral stabilization have been encouraging [17] some longterm results have revealed possible drawbacks [18,54], including increased lumbar lordosis, stretching of the Dacron parts, and malpositioning and loosening of pedicle screws leading to increased re-operation rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no objective assessment of the patients [8]. Grevitt et al [10] reported on 50 consecutive patients with a minimum follow-up of 19 months, who had symptomatic degenerative disc disease. The pre-operative Oswestry score of 59% improved to 31%.…”
Section: Discussionmentioning
confidence: 99%